Mediating effect of management information system on the relationship of warehouse attributes and its efficiency in Malaysia’s small and medium enterprises - Adam, Mohd Saifudin (2012)
This dissertation studies the relationship between the influential warehouse efficiency and warehousing attributes (operations, Human Capital Management or HCM, and layout), applied by the Small-Medium Enterprises (SMEs) manufacturing firms in Malaysia. These perspective research objectives are to determine whether there is any relationship between the warehousing attributes, warehouse efficiency, and warehousing Management Information System (MIS). It also examines the mediating effect of warehousing MIS in the relationship between warehousing attributes and warehouse efficiency. A quantitative method approach is applied in this research methodology. Nine hypotheses have been proposed for the research with data collected from the survey of 182 SME manufacturing firm owners in Malaysia as listed in the SME Directory 2009. The findings indicate that the warehousing MIS significantly mediates and has an effect on the warehousing attributes and their relationship with warehouse efficiency in the SME manufacturing firms. Theoretically, the research contributes to the growth development of the warehouse efficiency theories. Practically it could facilitate the owners or warehouse managers of the manufacturing firms in making the right management decisions regarding warehousing. For future research, the study recommends further exploration into the areas of security, environment, safety and health, waste management, and integrated system (International Standards Organisation or better known as ISO 9000, ISO 14000, and ISO 18000). As a conclusion, this study provides new knowledge and important insights of warehousing attributes that will benefit manufacturing firms and other related industries, particularly for SMEs in Malaysia